Variabilidade genética de Gymnotus inaequilabiatus (Valenciennes, 1839) (Osteichthyes, Gymnotiformes), da planície de inundação do alto rio Paraná e do rio Paraguai. - Rezende, Judy Ruiz (2007)
Gymnotus inaequilabiatus (Valenciennes, 1847) is distributed across the Paraná-Paraguai basin and in some coasts drainages of Uruguai and in southeast of Brazil. It inhabits either areas with grasses or floating macrophytes in small rivers and along the banks of larger dark water rivers. In Brazil, the common names of this species are; morenita, tuvira and sarapó, and it isn't a migratory species. From December 2005 until March 2006, 63 specimens were collected at upper Paraná River floodplain and 30 at Paraguay River. Ten enzyme systems (AAT: Aspartate aminotransferase, EST: Esterase, ADH: Alcohol dehydrogenase, GDH: Glucose dehydrogenase, SOD: superoxide dismutase, LDH: lactate dehydrogenase, G3PDH: glyceraldehyde 3-phosphate dehydrogenase, MDH: Malate dehydrogenase, SORB: Sorbitol dehydrogenase, IDH: Isocitrate dehydrogenase) were analyzed by starch gel electrophoresis technique. Seventeen loci were detected for each population. The population of upper Paraná River floodplain stream showed the biggest genetic variability either by proportion of polymorphic loci (76.47%), or by average number of alleles by locus (2,12 ± 0,86) and expected heterozygosity (0,2415 ± 0,2072). Some alleles were detected only in the upper Paraná River floodplain population: Adh-1(b), Adh-(c), Est-1(a), Est-2(a), Gdh-1(a), Gdh-1(c), Idh-1(b), Ldh-B(a), Mdh-A(c), Sod-1(b), Sod-2(b) e Sorb-1(b, c, d). The allele frequencies in the two populations are significantly different at 11 of the 17 loci. The Nei's genetic identity and genetic distance between the populations were I = 0,7889 and D = 0,2246, respectively. The data indicate these populations of the G. inaequilabiatus are diverging genetically and could be two distinct species in the future. A management program should inhibit the gene flux between them.